PENINGKATAN HASIL BELAJAR SISWA SMK NEGERI 6 MALUKU BARAT DAYA KELAS X PADA MATERI MATRIKS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING (DISCOVERY LEARNING) - Dolhalewan, Yosia; Ratumanan, Tanwey G; Ayal, Carolina S (Sora Journal of Mathematics Education, 2022)
Study this aim for knowing upgrade results study student class X SMKN 6 Southwest Maluku on the material Matrix with using the learning model invention guided (discovery learning). Subject in study this is student class X SMKN 6 Southwest Maluku , totaling 30 students . Study this is study action class with the teacher in the role as teacher and ongoing for 2 cycles . Data collection is carried out with use test and sheet observation . Data analysis techniques used is technique qualitative data analysis . Analysis result showing that occur enhancement results study from cycle I to cycle II, which is the value of end cycle I shows as many as 33.33% (10 students ), who obtained value 70, after that cycle II increases to 83.33% (25 students ). View results from cycle I and cycle II then has occur enhancement from cycle I to cycle II. With that 's the learning model invention guided (discovery learning) could increase results study student class X on the material Matrix